Karakteristik Gel Surimi Ikan Bulan-Bulan (Megalops Cyprinoides) Terhadap Frekuensi Pencucian - Sinuraya, Servinta Br; Zuraida, Ita; Diachanty, Seftylia; Irawan, Irman; Pamungkas, Bagus Fajar (Universitas Negeri Gorontalo, 2024)
The washing of fish meat in the manufacture of surimi is carried out to remove water-soluble components in order to obtain myofibrillar protein concentrate which plays an important role in the formation of surimi gel. This study aims to determine the frequency of washing that is able to produce the best surimi gel characteristics in Indo-Pacific Tarpon fish (Megalops cyprinoides). This study used a completely randomized design (CRD) with 4 washing frequency treatments and 3 replications. Parameters observed were proximate composition, gel strength, whiteness, and expressible moisture content. The frequency of washing had an effect on the characteristics of the fish surimi gel (p0.05) with the highest surimi gel strength in the one-wash treatment which had a load max value of 68.36±0.74 kg/cm2. The frequency of washing affects the gelling ability of this surimi.